MRI-based treatment plan simulation and adaptation for ion radiotherapy using a classification-based approach - Rank, Christopher M.; Tremmel, Christoph; Hünemohr, Nora; Nagel, Armin Michael; Jäkel, Oliver; Greilich, Steffen (Radiation oncology, 2013)
In order to benefit from the highly conformal irradiation of tumors in ion radiotherapy, sophisticated treatment planning and simulation are required. The purpose of this study was to investigate the potential of MRI for ion radiotherapy treatment plan simulation and adaptation using a classification-based approach.
Gesehen am 15.12.2021